PENGGUNAAN METODE DIALOG UNTUK MENINGKATKAN KEMAMPUAN DALAM MATERI PERCAKAPAN SEHARI-HARI PADA SISWA SMA - Mardani Mardani; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractFor the mandarin students, to study speaking skill is very important, especially the skill of daily speaking. Because the speaking skill of someone can influence communication ability with the other. Beside that, trained students speaking skill being one of responsibility mandarin teacher. writer in Raudhatul Ulum 1 Meranti found the students is not have bravery to using mandarin language and not have self confidence in communicated. For understand this condition, the writer want using “dialog methhod” to continued learning, the purpose of this method is to repair and improve students speaking ability. With pass pre test, three times doing trial learning and post test, the writer founded the “dialog method” succesfull to improve student speaking skill in mandarin language.Keywords: Daily speaking, Speaking skill, Self confidence